FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS KINERJA ORGANISASI - Alberd E. Pairikas (Universitas Riau, 2013)
Factors that effect the quality of organizational performance. Thisresearch aims to determine the effect of organizational ledership effectiveness,organizational structure, apparatus work motivation, determination of tax revenuetargets, availability of human resources and coordination on the quality oforganization’s performance SAMSAT Online Dinas Pendapatan dan Aset DaerahProvinsi Nusa Tenggara Timur. This research uses quantitative methods to test thehypothesis explanative. Samples amounted to 72 persons. Data collection usingquestionnaire techniques, while the data analysis using correlation and regressiontechniques. The test results show that the effectiveness of the role variablesapparatus work motivation, goal setting effectiveness of tax revenue, the willingnessof human resources and the effectiveness of coordination has a significant effect onimproving the quality Dinas Pendapatan dan Aset Daerah Provinsi Nusa TenggaraTimur, with a regression coefficient of 0,675 means the contribution of variableeffectiveness of work motivation apparatus, the effectiveness of the tax revenuetarget setting, preparation of human resources and the effectiveness of coordinationon the quality of the organization’s performance is omly 40,6% and the balance of59,4% is the contribution of the other variables wich in the turn can performed onthe following research.Key words: Organizational performance, leadership, organizational structure, humanresources, coordination.